DECENTRALIZED REGIONAL DEVELOPMENT BY INTER-MUNICIPAL COOPERATION IN INDONESIA CASE STUDY OF BARLINGMASCAKEB, JAVAPROMO AND KARTAMANTUL REGIONAL COOPERATION - PAMBUDI, WASIS ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Since the independence in 1945, Indonesia has been making continued effort for country’s economic and social development. The development is pursued along the comprehensive national development plans that reflect national policy and strategies for the achievement. The Asian Financial Crisis in 1997 attacked Indonesia not only economically but also politically. This political transition also significantly affected the way of development. The autonomous regional development in Indonesia spontaneously invites concept of the intermunicipal regional efforts over the local administration boundaries. In accordance with the shift of emphasis of national development towards decentralized bottom-up approach, several attempts of inter-municipal regional development have been practiced in Indonesia such as BARLINGMASCAKEB, JAVAPROMO and KARTAMANTUL. The findings shows for the intermunicipal regional cooperation aiming only for delivering improved public services collaboratively, the systemized discussions above may be sufficient. However, if the purpose of the inter-municipal cooperation is “development,” only meetings and discussions, even if it had taken the most sophisticated form, will not solve the problem. It needs more systematic approach to comprehensively cope with the “development issues” with solid functions of public management as follows. First of all, the regional cooperation has to have (a) common goal(s) to be pursued collaboratively. For carrying out the actions specified, there needs “financial” as well as “institutional” bases. The core requirement is an established solid body of operation and management. The function of that institution should involve (1) common goal (2) hierarchical plan of implementation, (3) financial arrangement (4) institutional preparation for implementation and management and (5) evaluation. From the viewpoint of the key aspects for success analyzed above, KARTAMANTUL is equipped with the core requirement and an established solid body of operation and management. To further promote effective effort of inter-municipal regional development, KARTAMANTUL can be regarded as one of the successful models as a driving force of the total development of Indonesia.